Finding God as a millennial - D.M. Struwig (Acta Theologica)
Currently, limited information is available on the spiritual inclinations of the millennial age bracket in South Africa. This research aims to fill this knowledge gap. The researcher proposes amalgamated ethnography as the method of inquiry for this project. The participants indicated strong feelings of conflict and rebellion that have inspired a spiritual quest for meaning and purpose as a method to assist with guiding behaviours, along with a need for connectedness with others. The participants are still in a developmental process and, currently, in a state of immature spiritual development. The researcher also stipulates the limitations and recommendations of this research and emphasises that this proposal should stimulate conversation and further research into the role of spirituality in the identity formation of millennials.